How Not to Read Philosophical Investigations: McDowell and Goldfarb on Wittgenstein on Understanding - Brandt, Stefan (Philosophical Investigations, 2014)
In a recent article, John McDowell has criticised Warren Goldfarb for attributing an anti-realist conception of linguistic understanding to Wittgenstein. I argue that McDowell is right to reject Goldfarb’s anti- realism, but does so for the wrong reasons. I show that both Goldfarb’s and McDowell’s interpretations are vitiated by the fact that they do not pay attention to Wittgenstein’s positive claims about understanding, in particular his claim that understanding is a kind of ability. The cause of this oversight lies in their endorsement of an excessively anti-systematic or “therapeutic” reading of Wittgenstein.

Introduction - Breunig, Anke; Brandt, Stefan (Wilfrid Sellars and Twentieth-Century Philosophy, 2019)
This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book explores Wilfrid Sellars’s relation to the mostly forgotten Oxford philosopher John Cook Wilson. It argues that Rudolf Carnap’s failure to give a unified account of logical and empirical meaning leaves him with a deficient account of logical meaning. The book also explores Sellars’s place within the analytic tradition and discusses Sellars’s conception of philosophy and the sense in which it embodies characteristically analytical ideas. It explains classical pragmatist influences on Sellars’s views by discussing aspects of the intellectual background in which those views developed. The book also argues that the key to Sellars’s truth pluralism is his analysis of truth as “semantic assertability”, which is motivated by the same consideration that leads him to adopt truth relativism. It concludes with a critical question about Sellars’s distinction between imagining and sensing.<br

Picture - Brandt, Stefan (Understanding Wittgenstein, Understanding Modernism, 2017)

Rezension von Christian Barth, David Lauer (Hrsg.), "Die Philosophie John McDowells. Ein Handbuch" - Brandt, Stefan (Zeitschrift für Philosophische Forschung, 2016)

Ryle on knowing how: Some clarifications and corrections - Brandt, Stefan (European Journal of Philosophy, 2020)
I argue for an account of know-how as a capacity for practical judgment—a view I derive from Gilbert Ryle. I begin by offering an interpretation of Ryle and by correcting a number of widespread misconceptions about his views in the current debate. I then identify some problems with Ryle's account and finally present my own view which, I argue, retains Ryle's insights while avoiding his mistakes.
CRIS-Team Scopus Importer:2020-08-14

Sellars and Quine on Empiricism and Conceptual Truth - Brandt, Stefan (British Journal for the History of Philosophy, 2016)
I compare Sellars’s criticism of the ‘myth of the given’ with Quine’s criticism of the ‘two dogmas’ of empiricism, that is, the analytic–synthetic distinction and reductionism. In Sections I to III, I present Quine’s and Sellars’s views. In IV to X, I discuss similarities and differences in their views. In XI to XII, I show that Sellars’s arguments against the ‘myth of the given’ are incompatible with Quine’s rejection of the analytic–synthetic distinction.
Keywords: Sellars; Quine; empiricism; myth of the given; analytic–synthetic distinction

Sellars and Wittgenstein on Following a Rule - Brandt, Stefan (Wilfrid Sellars and Twentieth-Century Philosophy, 2019)
I compare Sellars’s and Wittgenstein’s conceptions of following a rule of language. I begin by briefly speculating about the influence of Wittgenstein’s later writings on Sellars. I then compare the place of rules of language in their respective philosophies. Subsequently, I discuss and compare their notions of following a rule. I conclude by arguing that the differences in their views are the consequence of their different views on the causal role of reasons in the explanation of action.<br

Sellars and Wittgenstein on Following a Rule - Brandt, Stefan (Wilfrid Sellars and Twentieth-Century Philosophy, 2020)
CRIS-Team WoS Importer:2021-04-23

Verantwortliche Kontrolle und Ryleanische Regresse. Kommentar zu David Löwensteins Know-how as Competence - Brandt, Stefan (Zeitschrift für Philosophische Forschung, 2018)
Created from Fastlane, WoS look-up

Wilfrid Sellars and Twentieth-Century Philosophy - Brandt, Stefan; Breunig, Anke (Routledge, 2019)
This collection features eleven original essays, divided into three thematic sections, which explore the work of Wilfrid Sellars in relation to other twentieth-century thinkers. Section I analyzes Sellars’s thought in light of some of his influential predecessors, specifically Ludwig Wittgenstein, Rudolf Carnap, John Cook Wilson, and Kazimierz Ajdukiewicz. The second group of essays explores from different perspectives Sellars’s place within the analytic tradition, including his relation with analytic Kantianism and analytic pragmatism. The book’s final section extracts some of the most significant lessons Sellars’s work has to offer for contemporary philosophy. These chapters address his views on inference, his views on truth and its connection to recent discussions about truth-relativism and truth-pluralism, his conception of self-knowledge, and his theory of perceptual experience.<br

Wilfrid Sellars and Twentieth-Century Philosophy Introduction - Breunig, Anke; Brandt, Stefan (Wilfrid Sellars and Twentieth-Century Philosophy, 2020)
CRIS-Team WoS Importer:2021-04-23

Wittgenstein and Sellars on Intentionality - Brandt, Stefan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2011)
The aim of this thesis is to explore Ludwig Wittgenstein’s and Wilfrid Sellars’s view on intentionality. In the first chapter I discuss the account of intentionality and meaning the early Wittgenstein developed in his Tractatus logico-philosophicus. I present his idea that sentences are pictures of states of affairs with which they share a ‘logical form’ and to which they stand in an internal ‘pictorial relationship’. I argue that Wittgenstein thought of this relationship as established by acts of thought consisting in the operation of mental signs corresponding to the signs of public languages. In the second and third chapters I discuss the later Wittgenstein’s criticism of ideas at the heart of the Tractarian account of intentionality, as well as his explanations of the phenomena that motivated it. In the second chapter I examine his rejection of the idea that thinking consists in the operation of mental signs and his criticism of the idea that meaning and understanding are mental processes accompanying the use of language. In the third chapter I turn to Wittgenstein’s criticism of the idea that representations stand in an internal ‘pictorial relation’ to objects in the natural order that are their meaning. I illuminate his later views by discussing Sellars’s non-relational account of meaning, in particular his claim that specifications of meaning do not relate expressions to items that are their meaning, but rather specify their rule-governed role in language. I conclude with a discussion of the later Wittgenstein’s account of the relationship between intentional phenomena and the objects at which they are directed. In the final fourth chapter I provide a detailed discussion of Sellars’s account of thinking. I conclude with some criticisms of Sellars’s views.

Wittgenstein on Intentionality - Brandt, Stefan (A Companion to Wittgenstein, 2017)